2013
DOI: 10.3171/2013.2.spine12525
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between degree of focal kyphosis correction and neurological outcomes for patients undergoing cervical deformity correction surgery

Abstract: Object Reversal of the normal cervical spine curvature, as seen in cervical kyphosis, can lead to mechanical pain, neurological dysfunction, and functional disabilities. Surgical intervention is warranted in patients with sufficiently symptomatic deformities in an attempt to correct the deformed cervical spine. In theory, improved outcomes should accompany a greater degree of correction toward lordosis, although there are few data available to test this relationship. The purpose of this study is to determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 24 publications
(20 reference statements)
3
47
0
Order By: Relevance
“…Several publications have shown a correlation between deformity of the cervical spine and pain and functional disability, in addition to the intensity of the neurological deficit in patients with myelopathy. [14][15][16][17][18] Until now, no criteria have been defined for an indication of corrective surgery for spinal deformity, nor is there any standardization of the objectives of correction of deformity. 1 Recently, a classification system for cervical spine deformity was published, 19 considering the type of deformity and presenting modifiers, including three radiographic parameters, in addition to the severity of the myelopathy and the SRS-Schwab classification of adult deformity types.…”
Section: Introductionmentioning
confidence: 99%
“…Several publications have shown a correlation between deformity of the cervical spine and pain and functional disability, in addition to the intensity of the neurological deficit in patients with myelopathy. [14][15][16][17][18] Until now, no criteria have been defined for an indication of corrective surgery for spinal deformity, nor is there any standardization of the objectives of correction of deformity. 1 Recently, a classification system for cervical spine deformity was published, 19 considering the type of deformity and presenting modifiers, including three radiographic parameters, in addition to the severity of the myelopathy and the SRS-Schwab classification of adult deformity types.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical malalignment is debilitating and has adverse effects on the overall functioning and health-related quality of life (HRQOL) of the patient. 7,12,22,24,27,29 Tang and colleagues 27 investigated cervical positive sagittal malalignment (CPSM) and disability following posterior cervical fusion in 113 patients. The authors found that increasing CPSM correlates with increasing disability and determined a CPSM threshold of 4 cm, at which severe disability occurs.…”
mentioning
confidence: 99%
“…Postoperative hypotension has been proved as one direct reason of delayed cord dysfunction due to lowering tissue perfusion [5]. A great degree of kyphosis correction is also associated with late postoperative neurologic complication, for this may induce foraminal stenosis, enhance posterior drift or distraction of spinal cord [6,7]. Previous studies have indicated that patients with sagittal deformities, especially hyperkyphosis are at higher risks of neurologic deficits [8,9].…”
Section: Disscussionmentioning
confidence: 99%